2016
DOI: 10.1007/s10459-015-9663-4
|View full text |Cite
|
Sign up to set email alerts
|

How do interprofessional student teams interact in a primary care clinic? A qualitative analysis using activity theory

Abstract: Practice based interprofessional education opportunities are proposed as a mechanism for health professionals to learn teamwork skills and gain an understanding of the roles of others. Primary care is an area of practice that offers a promising option for interprofessional student learning. In this study, we investigated what and how students from differing professions learn together. Our findings inform the design of future interprofessional education initiatives. Using activity theory, we conducted an ethnog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…While activity theory has been used in considerations of team work in clinical settings [ 32 , 33 , 38 41 ] its use in IPL is relatively novel. Activity theory has been applied to communication [ 42 ], student clinical placements [ 43 ], and team debriefings [ 44 ], but not specifically to curriculum development and implementation. Our study has used activity theory to reveal contradictions and tensions in IPL curriculum development and delivery.…”
Section: Discussionmentioning
confidence: 99%
“…While activity theory has been used in considerations of team work in clinical settings [ 32 , 33 , 38 41 ] its use in IPL is relatively novel. Activity theory has been applied to communication [ 42 ], student clinical placements [ 43 ], and team debriefings [ 44 ], but not specifically to curriculum development and implementation. Our study has used activity theory to reveal contradictions and tensions in IPL curriculum development and delivery.…”
Section: Discussionmentioning
confidence: 99%
“…One theory that pays attention to interactions between the individual and the system is activity theory (Engeström et al 1999 ; Engeström 1987 ; Virkkunen and Newnham 2013 ). It has been proposed as a tool for studying complex issues in HPE (Varpio et al 2017 ) and has previously been applied to address different aspects of workplace learning (Reid et al 2015 ; de Feijter et al 2011 ; Larsen et al 2017 ) and group interactions (Kent et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…As stressed by Wan (2018), programs such as these must be developed at primary care centers because of the unique combination of resources available and good management achievable in such settings. Furthermore, programs managed at primary care centers usually achieve better continuity of obesity prevention activities, thereby favoring long term follow-up (Kent et al, 2016). Reinforcing this hypothesis, Grant et al (2017) reported that interventions led by primary care nursing professionals both at the individual and community level, provided greater access to care resulting in cost savings and helping to empower social change.…”
Section: Discussionmentioning
confidence: 99%